Promoting blended learning through eTeaching and Learning scholars - Herrington, Anthony; Schrape, Judith; Flintoff, Kim (AACE, 2010)
Blended learning is an approach to teaching and learning that is being promoted at many universities involving an integration of learning technologies and face-to-face teaching. This paper outlines a strategy for promoting blended learning that involves identifying eTeaching and Learning scholars and providing them with possibilities for engaging their students in learning with technology. The strategy employs an action learning approach that utilises the knowledge and experiences of participants to address a common problem: In what ways and to what to extent can blended approaches support student learning?